DECLINE TREND IN NUMERACY ACHIEVEMENT OF JUNIOR HIGH SCHOOL STUDENTS IN CENTRAL PAPUA: ANALYSIS OF EDUCATION REPORT CARD 2024–2025 - Ebit Rusali (RADJA PUBLIKA, 2025)
This research examines the declining trend in numeracy achievement among junior high school students in Central Papua based on the 2024-2025 Education Report. As the youngest province with challenging geographical characteristics, Central Papua faces complex problems in equitable quality education. The research aims to analyze the declining trend in numeracy achievement, identify determinant factors, and formulate contextual policy recommendations. Using a quantitative descriptive approach, this study analyzes secondary data from the Ministry of Education and Culture's Education Report using temporal comparative analysis, spatial gap analysis, correlational analysis, and factor analysis techniques. Results show a significant decrease in numeracy achievement from 48.54% (2024) to 45.96% (2025), contrary to the increasing national trend (57.42% to 59.75%). Five determinant factors include: lack of contextual teaching materials, low pedagogical literacy among teachers, limited supporting infrastructure, students' negative perceptions of mathematics, and low literacy skills as barriers to understanding numeracy problems. In conclusion, the declining trend in numeracy achievement in Central Papua requires holistic interventions including the development of teaching materials based on local wisdom, strengthening teacher capacity, improving supporting infrastructure, and an ecological approach involving various stakeholders to optimize the quality of numeracy education.